O026 Human papillomavirus (HPV) vaccination and STI screening in men who have sex with men (MSM). Clinical outcomes and factors associated with completion of a three dose schedule within one year in a clinical cohort. (30th June 2016) - McSorley, John; Gebru, Eden; Nehor, Roubinah; Shaw, Andew; Brook, Gary
Abstract : Background/introduction: We introduced HPV4 vaccination for younger MSM under 27 years into our sexual health services in 2012. We report on the attendance behaviour, clinical outcomes, completion rates and factors associated with vaccination completion in our cohort. Aims: (1) To deliver 3 dose HPV4 vaccination to younger MSM. (2) To increase engagement and STI testing by younger MSM at integrated sexual health services. Methods: HPV4 vaccine was offered at Time 0, 2–4 and 6–12 months, with STI testing, clinic call/recall, alongside care and support as appropriate. We conducted a retrospective electronic case note (EPR) review of all eligible MSM at end 2015. Completion rates are censored at 1 year. Results: 893/930 (96%) offered vaccine accepted 1 st dose. Discussion/conclusion: We observed 3 dose completion rates commensurate with outcomes expected from a catch up vaccination programme. Completion was associated with older age, HIV infection, prior known HPV infection, self-identifying homosexual men and non- white british ethnicities. We observed high rates of STI testing and infection in this cohort. Delivering HPV vaccination within sexual health care services is an effective engagement strategy for young MSM.